2019
DOI: 10.1038/s41598-019-47416-w
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced morphological and functional differences of pancreatic cancer with epithelial or mesenchymal characteristics in 3D culture

Abstract: Pancreatic cancer, composed of heterogeneous cancer cells, alters epithelial to mesenchymal features during growth and metastasis. In this study, we aimed to characterize pancreatic ductal adenocarcinoma (PDAC) cells showing epithelial or mesenchymal features in 3D culture. In 3D culture, PK-1 cells had high E-cadherin and low vimentin expression and exhibited a round-like appearance encircled by flat cells. PANC-1 cells had high vimentin and low E-cadherin expression and formed grape-like spheres. PK-1 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 26 publications
1
48
0
Order By: Relevance
“… 169 PDAC cells with intact TGF-β signaling machinery assume more EMT phenotype when cultured as spheroids compared to monolayer culture. 170 However, PDAC cells are also under constant interaction with surrounding cell types, and this can by mimicked by inclusion of CAFs, vascular endothelial cells and immune cells at various ratio to form heterotypic spheroids. 171 Furthermore, addition of ECM matrices in the culture is commonly used to increase stiffness of the culture media.…”
Section: Preclinical Models To Study Emtmentioning
confidence: 99%
“… 169 PDAC cells with intact TGF-β signaling machinery assume more EMT phenotype when cultured as spheroids compared to monolayer culture. 170 However, PDAC cells are also under constant interaction with surrounding cell types, and this can by mimicked by inclusion of CAFs, vascular endothelial cells and immune cells at various ratio to form heterotypic spheroids. 171 Furthermore, addition of ECM matrices in the culture is commonly used to increase stiffness of the culture media.…”
Section: Preclinical Models To Study Emtmentioning
confidence: 99%
“…Thus, autocrine/paracrine FGF19/FGFR4 signaling is not involved in regulating the expression of anticancer drug transporters and the resistance toward anticancer drugs in PDAC cells. Next, we examined sphere-forming ability, which is viewed as an indicator of self-renewal and stemness [ 43 , 44 , 45 ]. Sphere-forming assays showed that the number of spheres was not different between control and 2 μM BLU9931-treated PK-1 cells ( Figure 4 D).…”
Section: Resultsmentioning
confidence: 99%
“…Our findings suggest that FGF19/FGFR4 signaling had little association with stemness in PDAC cells ( Figure 4 ). Thus, FGFR4 and FGF19 expression was reduced in 3-D culture ( Figure 4 E), which is an optimal culture condition for CSCs [ 43 , 44 , 45 ], suggesting that FGF19/FGFR4 activation was not contributing to CSC formation. FGFR1 and FGFR4 are known to compete via their interactions with KLB [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include, but are not limited to, the presence of defined or tuneable extracellular matrix (ECM), the potential to include multiple cell types, and the opportunity to differentiate cells in response to spatiotemporal cues. Several groups have established that there are important morphological, biochemical and functional differences between cells cultured in 2D versus 3D ( Kenny et al, 2007 ; Sung et al, 2013 ; Shichi et al, 2019 ), suggesting there is scope to better understand native cellular behaviour using 3D assays.
Fig.
…”
Section: Methodologies Of 3d Organotypic Culturementioning
confidence: 99%